2007
DOI: 10.1016/j.ijnurstu.2005.11.026
|View full text |Cite
|
Sign up to set email alerts
|

From Husserl to van Manen. A review of different phenomenological approaches

Abstract: This paper traces the development of phenomenology as a philosophy originating from the writings of Husserl to its use in phenomenological research and theory development in nursing. The key issues of phenomenological reduction and bracketing are also discussed as they play a pivotal role in the how phenomenological research studies are approached. What has become to be known as "new" phenomenology is also explored and the key differences between it and "traditional" phenomenology are discussed. van Manen's ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
601
0
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 576 publications
(624 citation statements)
references
References 61 publications
0
601
0
23
Order By: Relevance
“…It means holistic understanding of human beings and giving prominence to the modalities and lifeworld concepts. The four fundamental concepts of the lifeworld based on Merleau-Ponty's ideas-lived space (spatiality), lived body (corporeality), lived time (temporality), lived human relation (relationality or communality) and lived things and objects (materiality) [28]-are important for phenomenological questioning, reflection, and writing in the research process [1,10,27,28]. Modalities are productive categories enabling reflecting, questioning and writing [1,25].…”
Section: Ontological Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It means holistic understanding of human beings and giving prominence to the modalities and lifeworld concepts. The four fundamental concepts of the lifeworld based on Merleau-Ponty's ideas-lived space (spatiality), lived body (corporeality), lived time (temporality), lived human relation (relationality or communality) and lived things and objects (materiality) [28]-are important for phenomenological questioning, reflection, and writing in the research process [1,10,27,28]. Modalities are productive categories enabling reflecting, questioning and writing [1,25].…”
Section: Ontological Reductionmentioning
confidence: 99%
“…She states that the radicality, complexity and discipline of the phenomenological attitude as a whole can be completely missed, especially by novice researchers. [21] also observe that researchers make no reference to some of the fundamental methodological keywords such as reduction and bracketing, using these terms synonymously or the same concept in different ways without distinguishing their specific meanings [10] presents an extensive review of different phenomenological approaches, also discussing reduction. [23] strives through the lens of Merleau-Ponty and [11] to explore differences among the descriptions of the phenomenological method by philosophers.…”
Section: Introductionmentioning
confidence: 99%
“…Health services research is increasingly embracing hermeneutics and recognizing that patient accounts of experiences in care can reflect hidden experience (Mackey, 2005). Merlau-Ponty expanded upon both Husserl and Heidegger to focus upon categorizing experience in discovering time, space, body, and relations (Dowling, 2007). Sartre focused upon the existence of self, which agrees with Mead's reification of self.…”
Section: Hermeneuticsmentioning
confidence: 92%
“…Sartre focused upon the existence of self, which agrees with Mead's reification of self. Van Manen suggested expanding rational inquiry to include an imaginative process where verification of theme occurs through elaboration (Dowling, 2007). Smith et al (2009) suggested that the "particular," or the individual experience, is recognizable in IPA because information is gathered and interpreted at the level of the person as opposed to being generalized at a group or population level.…”
Section: Hermeneuticsmentioning
confidence: 99%
See 1 more Smart Citation